ESTABLISHMENT OF A SUSTAINABLE SOCIAL SUPPORT-ORIENTED EMPLOYMENT AND ENTREPRENEURSHIP ECOSYSTEM IN THE NORTH MOROWALI NICKEL INDUSTRY REGION - Riadi, Slamet; Nawawi, Muh.; Haryanti, Tuti; Latifah, Ayi; Krisnamurti, Reza Mahendra (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
This study aims to investigate and evaluate Social Support in the development of a Sustainable Employment and Entrepreneurship Ecosystem within the North Morowali Nickel Industrial Area, focusing on (1) the Upstream-Downstream Employment and Entrepreneurship Ecosystem in the North Morowali Nickel Industry; (2) work plans and potential collaborations concerning Multistakeholder Entrepreneurship Initiatives in the North Morowali Nickel Industrial Area; and (3) Gap Analysis (Current Condition vs. Ideal Condition) in the North Morowali Nickel Industrial Area. This study employs a qualitative methodology utilizing a case study approach. Data collecting methods included online questionnaires, in-depth interviews with diverse stakeholders, focus group discussions (FGD) with stakeholder representatives, and document analysis. Thematic analysis was employed to discern the primary themes associated with social support and the employment and entrepreneurial ecosystem in the North Morowali Nickel Industry region.